2006
DOI: 10.1093/brain/awl149
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training is safe and improves exercise capacity in patients with mitochondrial myopathy

Abstract: Exercise intolerance is a prominent symptom in patients with mitochondrial myopathy (MM), but it is still unsettled whether exercise training is safe and beneficial for patients with MM. To address this, we studied the effect of 12 weeks cycle training on exercise capacity, quality of life and underlying molecular and cellular events in five patients with single large-scale deletions, one with a microdeletion and 14 with point mutations of mitochondrial DNA (mtDNA), and 13 healthy subjects. Each training sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
3
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(136 citation statements)
references
References 30 publications
10
118
3
5
Order By: Relevance
“…Endurance exercise training has also been found to be safe and improve peak exercise tolerance and cardiac and skeletal muscle function in conditions that share similar characteristics as BTHS: mitochondrial myopathies (Cejudo et al 2005;Jeppesen et al 2006Jeppesen et al , 2009 and congestive heart failure (Coats et al 1992;Delagardelle et al 2002;Giannuzzi et al 2003;Bartlo 2007). In patients with other mitochondrial myopathies, an endurance exercise program (3-5Â/week, 12 weeks, 70% VO 2peak ) increased peak oxygen consumption 23-29% and peak work rate 16-100% (Cejudo et al 2005;Jeppesen et al 2006Jeppesen et al , 2009. Also, 14 weeks of endurance exercise training increased peak oxygen consumption (~25%), peak skeletal muscle oxygen extraction (20%), and mitochondrial function, enzyme activity and volume (~50%) without an improvement in cardiac function in individuals with mitochondrial myopathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endurance exercise training has also been found to be safe and improve peak exercise tolerance and cardiac and skeletal muscle function in conditions that share similar characteristics as BTHS: mitochondrial myopathies (Cejudo et al 2005;Jeppesen et al 2006Jeppesen et al , 2009 and congestive heart failure (Coats et al 1992;Delagardelle et al 2002;Giannuzzi et al 2003;Bartlo 2007). In patients with other mitochondrial myopathies, an endurance exercise program (3-5Â/week, 12 weeks, 70% VO 2peak ) increased peak oxygen consumption 23-29% and peak work rate 16-100% (Cejudo et al 2005;Jeppesen et al 2006Jeppesen et al , 2009. Also, 14 weeks of endurance exercise training increased peak oxygen consumption (~25%), peak skeletal muscle oxygen extraction (20%), and mitochondrial function, enzyme activity and volume (~50%) without an improvement in cardiac function in individuals with mitochondrial myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, endurance exercise training in patients with non-BTHS heart failure was safe, improved survival (Belardinelli et al 1999), decreased hospitalization (Belardinelli et al 1999), and increased quality of life (Coats et al 1992;Tyni-Lenne et al 1996;Belardinelli et al 1999). Similarly, endurance exercise training has been found to be safe, improve exercise capacity, increase skeletal muscle oxygen extraction, and improve quality of life in individuals with other non-BTHS mitochondrial myopathies (Taivassalo et al 2001;Cejudo et al 2005;Jeppesen et al 2006Jeppesen et al , 2009. However, the effect of endurance exercise training on these measures in BTHS is unknown.…”
mentioning
confidence: 99%
“…thies [12]. As skeletal muscle is the major targets of regular endurance exercise, some investigations indicated that mitochondria may be the key of long-term exercises ameliorate diseases [13].…”
Section: Body Composition and Growth Ratementioning
confidence: 99%
“…Exercise promises to be an effective therapeutic intervention in patients with both primary and secondary mitochondrial disease. Although future clinical trials need to be performed, clinicians should be prescribing a supervised exercise program to patients affected by mitochondrial disease, as it has been found to be safe and effective as a therapy [33,34].…”
Section: Exercisementioning
confidence: 99%